Quincy Market, 1860-75 - American Stereoscopic Views (Tufts Archival Research Center, 2005)
Elevated-view east-northeast of Quincy Market, located between North and South Market Streets. Signage and awnings adorn the south elevation of the building. The east elevation of Quicy Market, visible along the center-left side of the image, faces Merchants Row. Horse-drawn wagons and carriages fill South Market Street. The facades of buildings lining the west side of Commercial Street are visible behind Quincy Market, in the background of the photograph. 3 x 2 7/8, 3 3/8 x 3 3/8 overall Stereographs